The epidemiology of back/neck/spine injuries in National Collegiate Athletic Association men`s and women`s ice hockey, 2009/2010 to 2014/2015 - Zupon, A. B.; Kerr, Z. Y.; Dalton, S. L.; Dompier, L. P.; Gardner, E. Z. (Research in Sports Medicine, 2018)
This study describes the epidemiology of back/neck/spine injuries in National Collegiate Athletic Association (NCAA) men`s and women`s ice hockey. Data from 66 NCAA men`s and 29 women`s ice hockey programmes (total of 147 and 67 team-seasons, respectively) were analysed from the NCAA Injury Surveillance Program during the 2009/2010-2014/2015 academic years. In the study period, 226 and 97 back/neck/spine injuries were reported in men and women, respectively, for injury rates of 0.56 and 0.65/1000 athlete exposures. Injury rates were higher in competitions than practices in men (injury rate ratio [IRR] = 4.22; 95% confidence interval [CI]: 3.24-5.49) and women (IRR = 2.49; 95% CI: 1.67-3.70). Most injuries occurred in the lower back/lumbar spine (men: 52.2%; women: 48.5%). There were notably low rates of fractures and sever